(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Warsan Shire, London’s first Young Poet Laureate, wrote her poem “Girls” exclusively for the campaign against Female Genital Mutilation (FGM) in Britain initiated by Fahma Mohamed and led by The Guardian. FGM, a ritual rooted in gender inequality, attempts to mutilate female sexuality which is extremely traumatic for the victims and may lead to acute or chronic physical or medical complications. FGM is a ritual mostly found in Africa, Asia and the Middle East. The poem portrays the pain and trauma a girl undergoes after mutilating her genitalia. FGM, a surviving practice from primitive tribalism, is even practiced in Europe and America by the refugees and immigrants. The psychological and emotional implications of this practice are to be considered which stays with the victims for the rest of their lives. The intense fear, helplessness, pain, horror, humiliation, and betrayal experienced by the girls undergoing FGM create in them multi-phase trauma.The patriarchal religious and cultural discourses inflict sexual frigidity upon the girls in theirattempt to control female sexuality. Shire’s lines transmit this trans-historical and intergenerational trauma not onlyto the victims but to the individuals and cultures unaccustomed to this human rights violation.